Analisis Konstribusi Pendapatan Usahatani Kelapa Dalam pada Perkebunan Rakyat di Tipologi Lahan Pasang Surut Provinsi Sumatera Selatan - Yudhi Zuriah Wirya Purba (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
This study aims to analyze the revenue comparison monoculture with polyculture farming patterns and the contribution of small holder coconut farming on the household income of families in tidal lowlands type A and B. The study was conducted in Banyuasin and Ogan Ilir Districts where tidal lowland is always inundated. Sample farmers were withdrawn usingproporsionate stratified random sampling. The number of sample were 120 farm house holds monoculture and polyculture farming patterns. The results showed that the income from monoculture and polyculture farming patterns was not significantly different. The coconut farm income in both monoculture and polyculture patterns made major contribution to the household income.